THE FORMATION OF PT-IR ALLOYS AND CU-PD-RICH SULFIDE MELTS BY PARTIAL DESULFURIZATION OF FE-NI-CU SULFIDES: RESULTS OF EXPERIMENTS AND IMPLICATIONS FOR NATURAL SYSTEMS - Peregoedova A.; Baker D.R.; Barnes S.-J. (My University, 2004)
We propose a model of high-temperature formation of platinum-group element (PGE) alloys from base–metal sulfides subjected to decreasing sulfur fugacity (fS2). For this purpose we experimentally investigated the effect of partial desulfurization of monosulfide solid-solution (Mss) with variable Ni and Cu contents on the distribution behaviour of Pt, Ir and Pd at 1000 °C. We partially removed sulfur from the PGE-bearing Mss using the “tube-in-tube” technique and pyrrhotite as an fS2 buffer. We found that Mss undergoing S loss can produce (1) Pt and Ir exsolution from the Mss matrix in the form of PGE-bearing alloys, (2) partial melting of the Cu–Ni-bearing Mss to form Fe-rich Mss, Cu–Ni–Pd-rich sulfide liquid and Fe–Ir–Pt alloy. Both of these processes are geologically important. The partial melting of the S-depleted sulfides could explain the presence of two types of sulfides found in the mantle, Mss-dominated sulfides and S-poor sulfides consisting mainly of pentlandite and chalcopyrite. We also suggest that the Cu–Ni–Pd-rich liquid formed by partial melting of the sulfides could migrate away from the Mss and Fe–Ir–Pt alloys thus spatially decoupling Ir–Pt and Cu–Pd as observed in reefs and mantle nodules. In addition, the formation of PGE alloys in response to the desulfurization processes potentially could occur (1) after pressure falls during transport of the basalt magma with entrained sulfide droplets; (2) after sulfur removal by S-undersaturated melts or fluids from PGE-enriched sulfide proto-ore; (3) after degassing of the sulfide droplets occurring in a sub-volcanic chamber and (4) as a result of sulfide interaction with chromite.